Ultrafine, self-crimp, and electret nano-wool for low-resistance and high-efficiency protective filter media against PM(0.3) - Li, Yuyao (J Colloid Interface Sci, 2020)
Frequent outbreaks of emerging infectious diseases (EIDs) make personal protective filter media in high demand. Electrospun nanofibrous materials are proved to be very effective in resisting virus-containing fine particles owing to their small fiber diameters; however, hindered by the intrinsic close-packing character of fine fibers, electrospun filters suffer from a relatively high air resistance, thereby poor breathing comfort. Here, we report a biomimetic and one-step strategy to create ultrafine and curly wool-like nanofibers, named nano-wool, which exhibit fluffy assembly architecture and powerful electret effect. By achieving the online self-crimp and in-situ charging of nanofibers, the curly electret nano-wool shows a small diameter of ~0.6 μm (two orders of magnitude lower than natural wool: ~20 μm) and an ultrahigh porosity of 98.7% simultaneously, together with an ultrahigh surface potential of 13260 V (one order of magnitude higher than previous filters). The structural advantages and powerful electret effect enable nano-wool to show excellent filtration efficacy (>99.995% for PM(0.3)) and low air resistance (55 Pa). Additionally, nano-wool can be easily scaled up, not only holding great industrial prospect in personal protective respirators, but also paving the way for developing next-generation wool in a cost-efficient and multifunctional form.